MANAJEMEN PEMASARAN PONDOK PESANTREN BERBASIS PROGRAM PENGABDIAN MASYARAKAT - sopwandin, iwan (J-MPI (Jurnal Manajemen Pendidikan Islam), 2019)
This study aims to describe the marketing management of Al-Fadlliyah Islamic boarding school. Marketing at this pesantren focuses on a cooperative approach and community service, so that not only the pesantren cottage benefits, but the community also benefits from the activity. This research method uses qualitative research with case study research type. Data collection techniques used are: interview, observation and documentation. The results show that: 1) the marketing management process at this boarding school is through 4 stages, namely: planning, implementing, monitoring and evaluating; 2) Implications of marketing management of Islamic boarding schools, namely: a) Islamic boarding schools have a good image in the community, b) an increase in the number of students, especially from regions originating from locations where PPM is conducted.